PERANCANGAN WEBSITE PENJUALAN MENGGUNAKAN METODE PROTOTYPE PADA TOKO AGEN BERAS - Shafirina Arsydini Shidqi; Gustin Setyaningsih; Ika Romadoni Yunita; Muhamad Awiet Wiedanto Prasetyo (Jurnal Riset Sistem Informasi, 2025)
Doa Ibu Rice Agent Shop is a business that focuses on food processing production, especially rice production. However, the sales system at rice agent shops still uses traditional methods. To overcome this problem, it is necessary to design website-based e-commerce that has effective user interaction with the use of e-commerce features that are easy to use and understood by users.  The data collection methods used in this research are interviews, observation, documentation, literature study and questionnaires. Meanwhile, the system development method created is using a prototype. The results of this research are in the form of a website-based e-commerce website at the Ibu Tambaksari Kidul Doa Rice Agent Store. Based on the results of a questionnaire to 10 respondents, the percentage of 78.4% was in the "agree" interval scale, so it can be concluded that the website created was in accordance with what was expected.